Assessment Of Efficacy Of Coleus Amboinicus In The Prevention Of Candida Colonization - Sekhar, Pavithra; M. Surenthar, M. Surenthar (Journal of Neonatal Surgery, 2024)
Candida species are opportunistic fungal pathogens responsible for a wide range of infections, particularly in immunocompromised individuals. Increasing resistance to conventional antifungal drugs has created a need for alternative therapeutic agents. Coleus amboinicus, a medicinal plant widely used in traditional medicine, contains various bioactive phytochemicals with antimicrobial properties. The present study aimed to evaluate the antifungal activity of ethanolic leaf extract of Coleus amboinicus against Candida parapsilosis, Candida tropicalis, and Candida albicans. Antifungal activity was assessed using the Kirby–Bauer disk diffusion method, and the minimum inhibitory concentration (MIC) was determined using a microdilution assay. The extract demonstrated antifungal activity against C. tropicalis and C. albicanswith zones of inhibition of 17 mm and 19 mm respectively at 50 µL concentration, while no activity was observed against C. parapsilosis. MIC analysis showed maximum inhibition (91.9%) at dilution 10⁻¹. These findings suggest that Coleus amboinicus possesses promising antifungal potential against selected Candida species and may serve as a natural alternative for managing Candida-related infections.